Les stratégies spatiales de la population haïtienne à Miami - Cédric Audebert (EchoGéo)
Haitian emigration has evolved within the growing dependency of Haiti from the United States throughout the XXth century. The Haitian migratory pattern took on the form of an international migratory field linking the source country with Miami, where the population from Haitian ancestry has recorded a rapid growth. In a Floridian metropolis branded with a strong « ethno-racial » and economic segregation, the newcomers originally settled in the impoverished Black inner city neighborhoods. The effects of the federal immigration policy has been contrasted, bringing about the withdrawal of immigrants into themselves in Little Haiti when the policy was unpropitious or allowing a residential mobility in times of relaxed legislation. Subsequently, the growing complexity of the Haitian immigration space, characterized by a rapid extension and change in its forms, is apparent through a dichotomy between the traditional enclave and the new suburban settlements. Resulting from an aggregation/segregation dynamics, Haitian spatial concentration in Miami found expression in particular settlement locations, where processes of territorialization have taken place. The mental and functional adaptation to the place of settlement aims at appropriating it by giving it a sense of belonging, and appears to be the first step to collective strategies of territorialization. The take over of a section of the metropolitan area and its affectation to social, commercial and political forms of representation aim at perpetuating the Haitian community’s  bond by creating cohesion, solidarity and sociality.